Comparación de los hábitos de vida saludable (prácticas y creencias) entre estudiantes de odontología y contaduría (2021)
Objective: To determine and compare healthy lifestyle habits (practices and beliefs) among dental and accounting students. Method: a cross-sectional descriptive observational study was carried out. It was applied to 94 undergraduate students of the academic program of dentistry and 92 students of the accounting faculty of the Antonio Nariño University, the Questionnaire of Practices and Beliefs about Life Styles was used, validated by Arrivillaga et al, divided into 2 categories: Practices and Beliefs, as well as 6 subcategories that are evaluated through 116 questions. Participation was voluntary.